THE CULTURAL AND RELIGIOUS FOUNDATIONS OF MIGRANT ENTREPRENEURSHIP: EXPLORING INTENTIONS AND INFLUENCES - Jenkins, Sarah Elizabeth; Robertson, Michael James (Research Journal of Economics and Sustainable Development, 2024)
This study examines the relationship between psychological contract violation (PCV), turnover intention (TI), and workplace deviance (WPD) among employees in the agriculture and food directorates of Kenya. Data was collected from 415 participants through structured questionnaires, and Cronbach Alpha and Factor Analysis were used to establish reliability and validity. Results from hierarchical regression models indicated that TI significantly mediates the relationship between PCV and WPD, while PCV had a negative influence on TI and TI had a positive effect on WPD. These findings highlight the crucial role of human resource managers in addressing the problem of TI and developing effective mitigation strategies to curtail WPD. The study underscores the importance of the psychological contract between employers and employees and the potential negative effects of contract violations which lead to high TI and WPD. Limitations of the study include the use of self-reported data and the focus on a specific sector in Kenya.